2010
DOI: 10.1186/1475-2840-9-41
|View full text |Cite
|
Sign up to set email alerts
|

Circulating oxidized low-density lipoproteins and arterial elasticity: comparison between men with metabolic syndrome and physically active counterparts

Abstract: BackgroundAccumulation of oxidized low-density lipoproteins in the intimae of arteries and endothelial dysfunction are key events in the development of atherosclerosis. Patients with metabolic syndrome are at high risk for cardiovascular diseases but the linkage between metabolic syndrome and atherosclerosis is incompletely understood. We studied whether the levels of oxidized LDL and arterial elasticity differ between metabolic syndrome patients and physically active controls.Methods40 men with metabolic synd… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
13
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(15 citation statements)
references
References 52 publications
2
13
0
Order By: Relevance
“…Thus, our placebo-controlled study substantiates the in vivo antioxidant effects of cranberry juice polyphenols in subjects with metabolic syndrome. Oxidized LDL and malondialdehyde are stable biomarkers of oxidative stress, especially indicating lipid oxidation, and have been strongly correlated with metabolic syndrome and coronary artery disease [21, 22]. Interestingly, baseline oxidized LDL in our subjects with metabolic syndrome were higher than the previously reported uncontrolled trials in healthy volunteers [5, 7], which confirms reported observations of elevated oxidative stress in metabolic syndrome [23].…”
Section: Resultssupporting
confidence: 86%
“…Thus, our placebo-controlled study substantiates the in vivo antioxidant effects of cranberry juice polyphenols in subjects with metabolic syndrome. Oxidized LDL and malondialdehyde are stable biomarkers of oxidative stress, especially indicating lipid oxidation, and have been strongly correlated with metabolic syndrome and coronary artery disease [21, 22]. Interestingly, baseline oxidized LDL in our subjects with metabolic syndrome were higher than the previously reported uncontrolled trials in healthy volunteers [5, 7], which confirms reported observations of elevated oxidative stress in metabolic syndrome [23].…”
Section: Resultssupporting
confidence: 86%
“…In a prospective study, baseline oxLDL levels were an independent predictor of cardiac death, nonfatal myocardial infarction, and unstable angina; patients in the highest quartile had a hazard ratio 3.15 times greater than did patients in the lowest quartile [45]. In addition, MetS subjects have higher levels of oxLDL than control subjects [46], although the number of MetS criteria was not shown to be associated with oxLDL levels [47]. Because the level of oxLDL circulating in the blood is very low, it is difficult to demonstrate its association with CVD risk factors; thus, the relationship between oxLDL and CVD risk factors has not been fully established [42].…”
Section: Discussionmentioning
confidence: 97%
“…PLT counts may be a potential marker associated 336 with MetS components [17], and our results showed the 337 same association between PLT and MetS for 36-50-year-338 old female subjects. 339 Subjects with MetS had elevated levels of oxidized LDL 340 [46]. Circulating oxidized LDL seems to express the level 341 of oxidative stress and associate with the risk factors of 342 MetS [47].…”
Section: U N C O R R E C T E D P R O O Fmentioning
confidence: 99%